2021
DOI: 10.1101/2021.10.08.462639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability is actively regulated in speech

Abstract: Although movement variability is often attributed to unwanted noise in the motor system, recent work has demonstrated that variability may be actively controlled. To date, research on regulation of motor variability has relied on relatively simple, laboratory-specific reaching tasks. It is not clear how these results translate to complex, well-practiced and real-world tasks. Here, we test how variability is regulated during speech production, a complex, highly over-practiced and natural motor behavior that rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Unfortunately, for speech articulation, work with experimental manipulations of feedback variability is only just starting to appear (see Tang et al, 2021 ), and the effect of manipulating the inter-trial variability of a specific parameter (e.g., frequency of one or more formants) on sensorimotor adaptation to a separate, predictable perturbation of the same parameter (e.g., a consistent formant shift) remains entirely unexplored. We therefore investigated whether an experimental magnification or attenuation of perceived inter-trial formant variability during speech production (a) leads to compensatory adjustments in produced formant variability, (b) induces changes in the temporal structure of formant adjustments across productions, and (c) affects subsequent auditory-motor learning when the speaker is exposed to a predictable formant-shift perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, for speech articulation, work with experimental manipulations of feedback variability is only just starting to appear (see Tang et al, 2021 ), and the effect of manipulating the inter-trial variability of a specific parameter (e.g., frequency of one or more formants) on sensorimotor adaptation to a separate, predictable perturbation of the same parameter (e.g., a consistent formant shift) remains entirely unexplored. We therefore investigated whether an experimental magnification or attenuation of perceived inter-trial formant variability during speech production (a) leads to compensatory adjustments in produced formant variability, (b) induces changes in the temporal structure of formant adjustments across productions, and (c) affects subsequent auditory-motor learning when the speaker is exposed to a predictable formant-shift perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies found that artificially altering perceived inter-trial formant variability in the auditory feedback resulted in compensatory changes in formant production variability, suggesting that inter-trial variability is actively controlled and regulated [ 95 , 96 ]. In the current FACTS design, the task target noise variable is defined by a configuration file rather than being actively controlled during simulations.…”
Section: Discussionmentioning
confidence: 99%